Regulation of myotube formation by the actin-binding factor drebrin - Mancini Annalisa; Sirabella Dario; Zhang Weijia; Yamazaki Hiroyuki; Shirao Tomoaki; Krauss Robert S (Skeletal Muscle, 2011)
Abstract Background Myogenic differentiation involves cell-cycle arrest, activation of the muscle-specific transcriptome, and elongation, alignment and fusion of myoblasts into multinucleated myotubes. This process is controlled by promyogenic transcription factors and regulated by signaling pathways in response to extracellular cues. The p38 mitogen-activated protein kinase (p38 MAPK) pathway promotes the activity of several such transcription factors, including MyoD and MEF2, thereby controlling the muscle-specific transcription program. However, few p38-regulated genes that play a role in the regulation of myogenesis have been identified. Methods RNA interference (RNAi), chemical inhibition and immunofluorescence approaches were used to assess the role of drebrin in differentiation of primary mouse myoblasts and C2C12 cells. Results In a search for p38-regulated genes that promote myogenic differentiation, we identified Dbn1, which encodes the actin-binding protein drebrin. Drebrin is an F-actin side-binding protein that remodels actin to facilitate the change of filopodia into dendritic spines during synaptogenesis in developing neurons. Dbn1 mRNA and protein are induced during differentiation of primary mouse and C2C12 myoblasts, and induction is substantially reduced by the p38 MAPK inhibitor SB203580. Primary myoblasts and C2C12 cells depleted of drebrin by RNAi display reduced levels of myogenin and myosin heavy chain and form multinucleated myotubes very inefficiently. Treatment of myoblasts with BTP2, a small-molecule inhibitor of drebrin, produces a phenotype similar to that produced by knockdown of drebrin, and the inhibitory effects of BTP2 are rescued by expression of a mutant form of drebrin that is unable to bind BTP2. Drebrin in myoblasts is enriched in cellular projections and cell cortices and at regions of cell-cell contact, all sites where F-actin, too, was concentrated. Conclusions Our findings reveal that Dbn1 expression is a target of p38 MAPK signaling during myogenesis and that drebrin promotes myoblast differentiation.